TANGGAPAN WISATAWAN MENGENAI AKSESIBILITAS KECAMATAN RUPAT UTARA KABUPATEN BENGKALIS RIAU - Muhamad Rizki; Andi M Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Bengkalis Regency has a potential tourist attraction.One of the attractions that have great potential is Marine Tourism in North Rupat District. So many tourists visit bengkalis district to enjoy the tourist attraction in bengkalis one of them is North Rupat District which has a long beach about 17 km, and has a beautiful view overlooking the straits of Malacca. This study aims to describe the condition of tourism accessibility in North Rupat Sub-district of Bengkalis Regency and to know the responses of tourists to accessibility in North Rupat Sub-district of Bengkalis Regency. This research uses quantitative method for analysis which try to give clear and detailed description based on facts found in the field through questionnaires and questionnaires distribution then drawn a conclusion. The questionnaires were distributed as many as 50 people. While data collection techniques in this study using observation, interviews. The results of this study indicate that the response of tourists about the accessibility of North Rupat Sub-district of Bengkalis Riau Regency is in the Less Good category with the total number of 2727 total is in the range 1891 - 2731. Keywords: Accessibility, Tourist, Northern Rupat